(16b-7)-5(3b+4)=-6

Simple and best practice solution for (16b-7)-5(3b+4)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (16b-7)-5(3b+4)=-6 equation:


Simplifying
(16b + -7) + -5(3b + 4) = -6

Reorder the terms:
(-7 + 16b) + -5(3b + 4) = -6

Remove parenthesis around (-7 + 16b)
-7 + 16b + -5(3b + 4) = -6

Reorder the terms:
-7 + 16b + -5(4 + 3b) = -6
-7 + 16b + (4 * -5 + 3b * -5) = -6
-7 + 16b + (-20 + -15b) = -6

Reorder the terms:
-7 + -20 + 16b + -15b = -6

Combine like terms: -7 + -20 = -27
-27 + 16b + -15b = -6

Combine like terms: 16b + -15b = 1b
-27 + 1b = -6

Solving
-27 + 1b = -6

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '27' to each side of the equation.
-27 + 27 + 1b = -6 + 27

Combine like terms: -27 + 27 = 0
0 + 1b = -6 + 27
1b = -6 + 27

Combine like terms: -6 + 27 = 21
1b = 21

Divide each side by '1'.
b = 21

Simplifying
b = 21

See similar equations:

| 2x-5(4x+12)=138 | | -3(8p+5)-2(5-23p)=3(5+7p) | | f+h(x)= | | -2(4b+1)+(9b-1)=0 | | 2(x-25)=3x | | 6x-3(7x-16)=-72 | | 2j-k=p-14 | | 2w+5+3=58 | | f(3)=2.5 | | f(2.5)=3 | | -6x+5(5x+4)=134 | | 5.8x+5=4.8x | | 40=7x-9 | | z+12.1=-5.9 | | (4x-20)=61 | | 9x+5x+4+9=5x+4+8x | | -4x-3(-4x-15)=117 | | 9n-6=12 | | 15p-19p=8 | | 24+197y=24+197*5 | | s+25=18 | | X+y=o | | 12h-5h=48 | | 36-6n=-6(1+2n) | | 5j+7j=144 | | 4+5*4=2f | | 6m+8+5m-5=85 | | 8x+2=2x-4 | | 3.6q-2.2-4.3q=-1.7q-4.4 | | -3=x-2x | | 2.7q-2.5-5.7q=-4.0q-3.9 | | 2(3x+2)=7x-4 |

Equations solver categories